Techno‐economic and life‐cycle assessment of a wood chips‐based organosolv biorefinery concept for production of lignin monomers and oligomers by base‐catalyzed depolymerization. (16th November 2021) - Zeilerbauer, Lukas; Lindorfer, Johannes; Süss, Raphaela; Kamm, Birgit
Abstract: More wood for technical valorization is to be expected in Europe over the coming years, due to climate change and the bark beetle. To further independence from fossil‐fuel resources a novel approach to the base‐catalyzed depolymerization (BCD) of organosolv lignin into monomers and oligomers, while maximizing yields and minimizing coke formation, was scaled up in a theoretical wood‐based biorefinery with a yearly input of 40 000 t of wood chips. Other process steps were modeled from the literature. A novel work‐up approach was evaluated under laboratory conditions, implemented, and compared with a simulation‐based pervaporation technique. The life‐cycle assessment (LCA) showed that the biorefinery provided a significantly lower global warming potential (GWP) (excluding biogenic carbon) than its fossil counterparts. Moreover, the majority of impacts on the other midpoint categories was also smaller than for the fossil reference. However, after allocating the GWPs, it was evident that subsequent conversion of the C6 fraction to value‐added products is necessary for optimal results. The discounted cash flow analyses for the biorefinery setups (40 to 400 kt year –1 ) showed that they were not profitable with prices based on fossil references. However, when using higher prices/t from the literature, such as €1615 for monomers, €2000 for oligomers, and €510 for C6 sugars, a positive net present value could be reached at approximately 100 000–120 000 t processed annually. Hence, the conclusion was that a biorefinery utilizing wood not only brings environmental benefits and a reduction in the use of fossil resources but can also be financially beneficial. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd